Beta cell lipotoxicity in the development of type 2 diabetes: the need for species-specific understanding - Thomas, Patricia; Gallagher, Meurig T.; Da Silva Xavier, Gabriela (Frontiers in Endocrinology, 2023)
The propensity to develop type 2 diabetes (T2D) is known to have both environmental and hereditary components. In those with a genetic predisposition to T2D, it is widely believed that elevated concentrations of circulatory long-chain fatty acids (LC-FFA) significantly contribute towards the demise of insulin-producing pancreatic β-cells -the fundamental feature of the development of T2D. Over 25 years of research support that LC-FFA are deleterious to β-cells, through a process termed lipotoxicity. However, the work underpinning the theory of β-cell lipotoxicity is mostly based on rodent studies. Doubts have been raised as to whether lipotoxicity also occurs in humans. In this review, we examine the evidence, both in vivo and in vitro, for the pathogenic effects of LC-FFA on β-cell viability and function in humans, highlighting key species differences. In this way, we aim to uncover the role of lipotoxicity in the human pathogenesis of T2D and motivate the need for speciesspecific understanding.